Gambaran Konsumsi Makanan Fungsional dan Konsumsi Herbal pada Pasien Rawat Jalan Lansia di Rsud Berkah Pandeglang - Luh Desi Puspareni; Sofia Wardhani; A'immatul Fauziah (Nutriology : Jurnal Pangan,Gizi,Kesehatan, 2020)
Elderly was vulnerable to has diseases due to decreased physiological function of the body. In addition to medical and pharmacological therapies, the consumption of functional and herbal foods is an alternative or complementary choice for recovery. This research was an observational analytic study with a quantitative descriptive design with a total of 38 respondents. The results showed that respondents consumed functional foods with fruits, consumed 1-2 times a week, consumption duration of more than 1 year, consumed with the aim of curing the disease, and the main source of information came from the community or hereditary beliefs. Respondents consume herbs as complementary medicine. The types of herbs that are consumed the most are rhizomes, consumed 1-3 times a day, more than 1 year duration, and herbal related information obtained from the community or hereditary beliefs. These functional and herbal foods generally contain antioxidants and other compounds that have anti-inflammatory activity.